Ionic Liquid‐Assisted Anchoring SnO2 Nanoparticles on Carbon Nanotubes as Highly Cyclable Anode of Lithium Ion Batteries. Issue 14 (11th May 2020) - Liu, Kuiming; Zhu, Shengming; Dong, Xufeng; Huang, Hao; Qi, Min
Abstract: The commercialization of SnO2 ‐based anode materials for lithium ion batteries (LIBs) has been hindered by the huge volume change and fast capacity fading. Ionic liquid (IL)‐assisted strategy for the synthesis of SnO2 @IL‐modified carbon nanotubes (SnO2 @IL–carbon nanotubes (CNTs)) hybrid nanostructure is proposed with the SnO2 nanoparticles uniformly and strongly grafting on the CNTs. With low surface tension, IL as the solvent is beneficial to the dispersion of CNTs and the formation of small SnO2 nanoparticles, thus improving the interface contact between SnO2 and CNTs. Furthermore, the interface interaction can be also strengthened by IL‐assisted interface modification, substantially facilitating the electron/ion transport in SnO2 and meanwhile preventing its continuous volume change during lithiation. When used as the anode for LIBs, SnO2 @IL–CNTs achieve a high reversible capacity of 1438.1 mA h g −1 with an excellent cycling stability (800 cycles). Abstract : Hybrid nanostructure with the SnO2 uniformly and strongly grafting on the carbon nanotubes (CNTs) is successfully constructed through ionic liquid (IL)‐assisted strategy. The strategy substantially strengthens the interface interaction between SnO2 and CNTs and facilitates the electron/ion transport in SnO2, preventing its continuous volume change and capacity fading during lithiation. Thus, SnO2 @IL–CNTs anode for lithium ion batteries (LIBs) exhibits excellent electrochemical performance.